Cyber security awareness for CEOs and management - Willson, David (Lawyer) (Syngress is an imprint of Elsevier, 2016)
Cyber Security for CEOs and Managment is a concise overview of the security threats posed to organizations and networks by the ubiquity of USB Flash Drives used as storage devices. It covers information security, data protection and data breaches. The book provides an overview of the cyber threat and presents a discussion of the risk and threats to company information, customer information, and the company itself. It suggests how to lower the risk of a breach, reduce the associated liability, react quickly, protect customer information and the company's reputation. It addresses the company's ethical, fiduciary and legal obligations.